Analytical Study of Khalid Alig's Poetry - Ahmed Kamboh, Perwaiz; Arif Pathan, Muhammad; Ali Jarah, Ayaz (sourcecoder, 2022)
Khalid Alig is one of the great poets of Pakistan. The greatest virtue of his poetry is that he made his poetry known to the people. Where the elements of pain are evident in poetry, the same resistance poetry is evident on its own. Khalid Alig's poetry we also see the beautiful creation of aesthetics along with revolution, resistance, constant struggle. He is not a poet of struggle. The center of Khalid Alig's poetry was not only Pakistani society but he was a universal poet. Khalid Alig raised his voice for every oppressed person.